The Consequences of Mining Damage and their Impact on the Natural Environment – a Case Study of Trzebinia - Krzysztof Cygańczuk; Jacek Roguski (Safety & Fire Technology)
Aim: This article attempts to present issues related to surface subsidence in areas of closed and inactive coal and lignite mines. Land reclamation is the necessity of degrading the natural environment and restoring it to its original state. Introduction: Europe is giving up fossil fuels to reduce CO2 emissions into the atmosphere. It is also a result of the embargo imposed on 24 February 2022 on the Russian Federation on coal exports to European Union countries. This results in the search for alternatives to fossil fuels in all sectors of the economy. The direction of the search is towards choosing "green energy", which, due to its potential wide application, is already being treated as an instrument of climate neutrality. Many EU countries have decided to achieve climate neutrality by 2050, which means reducing greenhouse gas emissions by approximately 95% compared to the baseline year of 1990. However, achieving climate neutrality will require eliminating emissions not only in the electricity sector, but also in other sectors. As a result of this process, further areas requiring action after the mines are closed will be created, especially in Upper Silesia. Reclamation of post-mining areas is a very difficult task because there is no universal method of planning reclamation. Many forms of environmental degradation have been observed during mining activities. Methodology: The article uses theoretical and practical research methods, including the analysis of a report on satellite methods, which was developed on the basis of data from satellite radar interferometry. The land surface movement system belongs to the group of products of the Copernicus program, which involves monitoring the land surface, and its implementation was commissioned by the European Environment Agency (EEA). Moreover, the article was based on publications by domestic and foreign authors, authorities in the field of environmental engineering. Conclusions: Methods for reducing the negative impact of mining on the environment have long been developed and improved at all stages of mining activity, from reconnaissance work to the closure of a mining plant. One of the ways to reduce the negative impact of mining on the world's environment is the recultivation of post-mining areas, thanks to which the areas transformed due to mining activities are restored to their utility or natural values. Keywords: post-mining areas, environmental degradation, reclamation, land regeneration